Abstracts from the IOC World Conference on Prevention of Injury & Illness in Sport (British Journal of Sports Medicine, 2011)
The conference provides the world's leading sports medicine experts with an opportunity to present their work to an international audience of physicians, therapists, scientists and coaches.